How to assess water quality change in temperate headwater catchments of western Europe under climate change: examples and perspectives - Gascuel-Odoux, Chantal; Fovet, Ophélie; Faucheux, Mikaël; Salmon-Monviola, Jordy; Strohmenger, Laurent (Comptes Rendus. Géoscience)
Climate change effects on water quality are related directly and indirectly to the water cycle and human activities. We present examples of these effects using a retrospective analysis across European catchments according to three objectives: (i) identification of extreme or anomalous values in climatic and chemical variables at multiple time scales, (ii) assessment of variability in seasonal and inter-annual chemical cycles, and (iii) identification of a general water chemistry response to the North Atlantic Oscillation. From these examples, we highlight four challenges for research on the relationships between climate and water quality: (i) developing functional typologies of chemical elements, (ii) performing multi-temporal and multi-spatial analysis by aggregating data into water-cycle periods, (iii) decoupling effects of climate conditions and human activities by testing hypotheses using parsimonious models, and (iv) incorporating water quality and aquatic ecosystem health into integrated models. Water quality integrates current and past (legacy) conditions, flow pathways, and biogeochemical reactivity, which themselves depend on the climate. As our results highlight, water quantity and quality need to be studied together.